Toward good practice: A review of money advice services and debt management systems in Ireland, the United Kingdom, France and Germany - Stuart Stamp (United Nations Research Institute for Social Development (UNRISD), 2023)
Over-indebtedness, defined as the inability for a household to meet both essential living expenses and debt repayments, continues to be a significant phenomenon throughout Europe. The problem plays out differently in various countries depending on the relevant credit market, culture around money, regulatory environment and level of owner occupation, but remains strongly associated with poverty and structural inequalities within society. This scoping paper analyses lessons and good practices that can be learned from the provision of financial advice, debt counselling and debt management in the Republic of Ireland, the United Kingdom (England and Wales), France and Germany. When viewed comparatively, the four case studies offer unique insights into the advantages and disadvantages of various debt services available on the continent, and what a future of money advice services could look like when human rights, empowerment and equality are built in my design. This scoping paper is prepared for the development of a future project on personal and household debts under UNRISD's Alternative Economies for Transformation Programme (2021-2025) and is coordinated by the Credit Counselling and Recovery Service (CCRS) and the Association for Supporting the SDGs for the United Nations (ASD).
Keywords: 330; Schuldenmanagement; Anlageberatung; Private Verschuldung; Insolvenz; Irland; Großbritannien; Frankreich; Deutschland